Analysis of a reactive agility test using a live tester - Willey, B. J.; Young, W. B.; O`Brien, B. J. (Journal of Australian Strength and Conditioning, 2019)
This investigation revealed that the between subject variability within a session, and the test-retest reliability of the live reactive agility test-presenter, confounded the subject`s agility measure of total test time.